Roland Barthes' Semiotics Analysis on the Film "Nanti Kita Cerita Hari Ini" (NKCTHI) by Angga Dwimas Sasongko - SelviYani - Nur fahida (Cinematology: Journal Anthology of Film and Television Studies, 2021)
Film in a narrow sense is the presentation of images through a wide screen, but in a broader sense it can also include those broadcast on TV. Film is one of the mass media in the form of audio-visual and its nature is very complex. The film becomes a social discourse with unique characteristics that spread to various places, and the psychoanalytic perspective of film to influence the way of thinking related to perception and value suitability in which the information is communicated. Films in general also raise a theme or phenomenon that occurs in the midst of society. One of them is the film "Nanti Kita Cerita Hari Ini" (NKCTHI) directed by Angga Dwimas Sasongko. The film Later We Tell Today (NKCTHI) is the 13th film directed by Angga Dwimas Sasongko which was adapted from the book of the same name by Marchella FP. Unlike other film adaptations, NKCTHI's book only contains quotable words. The touching messages in this book are then turned into a scenario in the form of a complete story. In this study used qualitative research methods using the method of Content Analysis or content analysis. The main instrument in this study is the researcher himself who conducts direct research such as watching, listening and understanding the film "Nanti Kita cerita Hari Ini" (NKCTI), using Roland Barthes' semiotic theory, which focuses on the idea of two orders of signification. ). There are three aspects that show that in the film "Nanti Kita Cerita Hari Ini (NKCTHI)" it does not only have a general meaning but also has a denotative meaning, connotative meaning and myth.